Stress is not so bad—cortisol level and psychological functioning after 8-week HIIT program during pregnancy: a randomized controlled trial - Wilczyńska, Dominika; Walczak-Kozłowska, Tamara; Santos-Rocha, Rita; Laskowski, Radosław; Szumilewicz, Anna (Frontiers in Public Health, 2024)
Background Amid extensive pregnancy exercise research, the impact of High Intensity Interval Training (HIIT) on pregnant women’s mental health is underexplored. Despite exercise benefits, it can trigger stress responses like elevated cortisol. This study fills the gap by investigating correlations between hair cortisol levels, mental health, and HIIT effects in pregnant women. Methods We conducted a randomized control trial among 38 Caucasian women in uncomplicated, singleton pregnancy (age 31.11 ± 4.03 years, 21.82 ± 4.30 week of gestation; mean ± SD). The experimental group comprised 22 women engaged in an 8-week high-intensity interval training program (HIIT). The comparative group consisted of 16 pregnant women undergoing an 8-week educational program (EDU). Before and after the interventions, all women were evaluated using the following tools: Hair cortisol level measurements, Beck Depression Inventory – II for depressive symptoms assessment, Childbirth Attitudes Questionnaire for childbirth fear measurement, 12-item Short Form Health Survey to gage health-related quality of life, International Physical Activity Questionnaire for physical activity level estimation, and a Progressive maximal exercise test to evaluate maternal exercise capacity. Results The key finding of our study reveals that women engaged in the HIIT intervention exhibited a distinct cortisol production pattern in contrast to the EDU group practicing standard moderate intensity physical activity. In the HIIT group, there was an increase in hair cortisol levels, while the EDU group showed a notable decrease. Remarkably, HIIT stimulated cortisol production without adversely impacting fear of childbirth and psychophysical condition during pregnancy. In fact, only the HIIT group showed a significant enhancement in mental health. Conclusion No links were discovered between hair cortisol levels and the severity of depressive symptoms, psychophysical well-being, or fear of childbirth. Hence, based on our research, employing cortisol levels during pregnancy as an indicator of negative stress or depression risk appears unwarranted.